Sports tourism: terminological discussion - Mokras-Grabowska, Justyna (Turyzm/Tourism, 2016)
This article is a terminological discussion concerning sports tourism and those experts who stress its complexity, multifacetedness and heterogeneity. They distinguish between passive and active participation in sports disciplines and at the same time stress the huge role this form of tourism plays in stimulating regional development, mostly due to organizing mass events. This paper is based on the statements of eight experts from different research centres dealing with tourism (mainly sports tourism) accompanied by the authors’ attempt to ‘standardise’ them by referring to the subject literature.